The leader – manager debate in the Greek public administration: a critical review of the literature and future research agenda. - Tzavella, Vassiliki (International Conference on Business and Economics - Hellenic Open University, 2023)
One factor that researchers regularly cite as one of the most important contributors to organizational performance is leadership. However, despite the widespread speculation that leadership is important for organizational success, there has been relatively little research regarding the impact of leadership behaviours on organizational performance in governmental entities. More specifically, there is little research examining the impact of transformational leadership behaviours on organizational performance within governmental entities. The point is to examine the leader – manager debate in the field of Public Administration in Greece, in the light of the implementation of the New Public Management. Consequently, the purpose of this paper is to make a bibliographic review of these issues in the case of Greece, summarizing definitions and characteristics of leadership, leadership styles, differences between management and leadership styles and to study the challenge of public sector leadership in a time of crisis, the impact of New Public Management in the public sector administration as well as the leader / manager debate in the Greek public administration context. Τhe debate about Greece is being developed in the modern dimensions of the governance and administration of the quality of the institutions, that is in the modern results of good management and leadership. Through an illustrative bibliographic review we have conducted so far, there is a lack of studies about the impact of Greek public sector leadership, the existence of a best leadership style and whether the regional government can work effectively in terms of private sector management to be effective and rewarding in the local community. We base our study on Van Wart’s (2003) literature review on public sector leadership. Does public sector leadership existing in its own right, or is it merely private leadership applied to the public domain? Is there any need for leadership development programs which focus on the difference between administrative leaders in the public sector and their counterparts in the business world? What is the best leadership style to use in a time of crisis? Keywords: Leadership, Management, Local Government, Greek Public Administration, New Public Management.